Libraries in Continuing Education Centres: Life-Long Learning Facilities for Rural People in India - K. Sudha Rani; T. Ananda; G. Umapathi (University of Sofia, 2012)
The key aim of the establishment of Adult Education centers is to promote literacy and foster informal learning so that the adults are empowered to pursue any educational endeavor that they wish to undertake. The success of Adult Education Centre depends upon the kind of programms and activities conducted by it. In order to improve the quality of life of the people, and to keep them abreast of knowledge, libraries are being established in Adult Education Centres. The purpose of the establishment of library will serve only if the learners utilize it properly. Otherwise the effort may not be meaningful In view of this, a study was under taken on provision and the utilization of library services in adult education centres. 120 beneficiaries from 12 centres of six Mandals of Chittoor District of Andhra Pradesh State were selected as the sample and the findings and suggestions were presented in the paper.